Double-ion polymer, preparation method thereof and antibacterial coating composition containing double-ion polymer

By developing a dual-ion polymer containing an acrylate group and making it free radicals through water plasma treatment, the problem of insufficient hydrophilicity of the existing polymer materials is solved, and an antibacterial coating with excellent adhesion is achieved on the surface of the substrate, which significantly improves the adhesion and antibacterial effect of the antibacterial coating.

CN119591789APending Publication Date: 2025-03-11TAIWAN SOKOU INDS KOFUN YUUGENKOUSHI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311165530.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When existing polymer materials improve the adhesion of antibacterial coatings, long-chain non-ionic fragments reduce the hydrophilicity of polymers, limiting their solubility and application range in water.

Method used

A biion polymer containing an acrylate group has been developed, which has free radicals by aqueous plasma treatment, thereby forming an antibacterial coating with good adhesion on the surface of the substrate.

Benefits of technology

This dual-ion polymer has high hydrophilicity, is soluble in water, and forms an antibacterial coating with excellent adhesion through water plasma treatment, which significantly improves the adhesion and antibacterial effect of the antibacterial coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004442052850000021
    Figure BDA0004442052850000021
  • Figure BDA0004442052850000041
    Figure BDA0004442052850000041
  • Figure BDA0004442052850000051
    Figure BDA0004442052850000051
Patent Text Reader

Abstract

The invention relates to a diionic polymer, a preparation method thereof and an antibacterial coating composition containing the diionic polymer. The double-ion polymer contains an acrylate group and has high hydrophilicity, so that the double-ion polymer can be dissolved in water, and the double-ion polymer has free radicals through water plasma treatment, so that the antibacterial coating with excellent adhesiveness can be formed on the surface of a base material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a double ion polymer, in particular to a highly hydrophilic double ion polymer, a preparation method thereof and an antibacterial coating composition containing the double ion polymer. Background Art

[0002] With the improvement of public health systems and the improvement of medical standards, deaths caused by pathogens (such as viruses, bacteria or fungi, etc.) have dropped significantly. However, in recent years, with the development of jungles and forests, the increase in wildlife trade, more frequent human interactions and migrations, and / or the abuse of antibiotics, emerging infectious diseases, reemerged infectious diseases and / or drug-resistant bacteria still threaten human health.

[0003] In order to reduce the threat of pathogens, the hygienic safety of daily necessities has received more and more attention, so there are more and more products that form antibacterial coatings on the surface of daily necessities. Existing polymer materials for antibacterial coatings may contain diionic fragments, which can form a hydration layer on the surface of an object, thereby preventing pathogens from adhering to the surface of the object. In order to improve the adhesion of the antibacterial coating to the surface of daily necessities, this existing polymer material usually also contains long-chain non-ionic fragments to form non-covalent bonds such as van der Waals forces on the surface of the object. However, long-chain non-ionic fragments will reduce the hydrophilicity of the polymer, making the polymer insoluble in water, resulting in limited applications of existing polymer materials.

[0004] Therefore, there is an urgent need for a dual-ion polymer to solve the above problems. Summary of the invention

[0005] Therefore, one aspect of the present invention is to provide a diionic polymer, which contains an acrylate group and is highly hydrophilic, so it can be dissolved in water, and is treated with water plasma to make the diionic polymer have free radicals, which helps to form an antibacterial coating with good adhesion on the surface of the substrate.

[0006] Another aspect of the present invention is to provide a method for preparing a diionic polymer to obtain the diionic polymer.

[0007] Another aspect of the present invention is to provide an antibacterial coating composition comprising the above-mentioned dual ion polymer.

[0008] According to the above aspect of the present invention, a diionic polymer is provided, comprising the copolymer described in Formula 1.

[0009]

[0010] R 1 is a thioether containing at least two acrylate groups. 2 and R 3is a hydrogen atom or a methyl group. 4 are COOR' and CONR", and R' and R" are betaine, sulfobetaine or carboxybetaine.

[0011] In one embodiment of the present invention, R 1 Yes (CH2) x S(CH2) y CH(COOC2H3)2 or (CH2) x S(CH2) y CH(COOC2H3)CH2(COOC2H3), x is an integer from 0 to 5, and y is an integer from 0 to 5.

[0012] In one embodiment of the present invention, the average molecular weight of the diionic polymer is 5,000 to 10,000.

[0013] In one embodiment of the present invention, the contact angle of the antibacterial coating formed by the dual-ion polymer to water is 10° to 40°.

[0014] According to the above aspect of the present invention, a method for producing a diionic polymer is provided. First, a starting material is provided, wherein the starting material comprises a first monomer and a second monomer. The first monomer comprises a thioether having at least two hydroxyl groups. The second monomer comprises a betaine group, a sulfobetaine group or a carboxybetaine group. Next, a first polymerization step is performed on the starting material, an olefin compound containing an acyl halide group is added, and a second polymerization step is performed to obtain a diionic polymer.

[0015] In one embodiment of the present invention, the first monomer is CH2CH(CH2) m S(CH2) n CH(OH)2 or CH2CH(CH2) m S(CH2) n CHOHCH2OH, m is an integer from 0 to 5, and n is an integer from 0 to 5.

[0016] In one embodiment of the present invention, the acyl halide group comprises an acyl chloride group or an acyl bromide group.

[0017] In one embodiment of the present invention, the molar ratio of the first monomer to the second monomer is 2:3 to 3:2.

[0018] According to another aspect of the present invention, an antibacterial coating composition is provided, comprising the above-mentioned dual-ion polymer.

[0019] In one embodiment of the present invention, based on the usage of the antibacterial coating composition being 100 weight percent, the usage of the dual ion polymer is 30 weight percent to 50 weight percent.

[0020] The diionic polymer, its manufacturing method and antibacterial coating composition containing the same of the present invention are applied, wherein the diionic polymer contains an acrylate group and has high hydrophilicity, so it can be dissolved in water, and is treated with water plasma to make the diionic polymer have free radicals, which helps to form an antibacterial coating with good adhesion on the surface of the substrate. DETAILED DESCRIPTION

[0021] As mentioned above, the present invention provides a dual-ion polymer, a method for preparing the same, and an antibacterial coating composition containing the same. The dual-ion polymer contains an acrylate group and is highly hydrophilic, so it can be dissolved in water and treated with water plasma to make the dual-ion polymer have free radicals, thereby helping to form an antibacterial coating with good adhesion on the surface of the substrate.

[0022] The "high hydrophilicity" described herein means that the diionic polymer has a high affinity for water, so it can be dissolved in water, and the surface of the antibacterial coating formed can form a water film with water. In some embodiments, high hydrophilicity can be evaluated by the solubility of the diionic polymer in water and / or the contact angle of the antibacterial coating formed on water. In some embodiments, high hydrophilicity can be expressed, for example, as the solubility of the diionic polymer in water is greater than 10g / 1000mL of water at 20°C. In some embodiments, high hydrophilicity can be expressed, for example, as the contact angle of the antibacterial coating formed by the diionic polymer with water is less than or equal to 40°, such as: 10° to 40°.

[0023] The "good adhesion" described herein refers to the tight adhesion, bonding or attachment between the antibacterial coating formed by the dual-ion polymer and the surface of the substrate. In some embodiments, the adhesion can be evaluated using a cross-sectional test, which is to use a sharp knife to carve multiple lines in two different directions on the surface of an object, then stick a pressure-sensitive tape on the surface of the object where the lines are located, and then quickly pull the tape from the surface of the object to observe whether the surface of the object peels off. In some embodiments, good adhesion means that after the tape is quickly pulled off, there is no antibacterial coating peeling off from the substrate, or peeling only occurs around the lines or at the intersection of the lines, and the peeling area is less than 5%.

[0024] In other embodiments, adhesion can be evaluated using a steel wool test, which is to evaluate the weight loss rate of the surface of the object after rubbing the surface of the object with steel wool with a load, wherein the weight loss rate is the percentage of the weight difference of the surface of the object before and after the steel wool is rubbed and the weight of the surface of the object before the steel wool is rubbed. The steel wool test is performed with different loads and different friction times to compare the durability of the surfaces of different objects to multiple frictions. In some specific examples, the weight loss rate of the surface with good adhesion is less than 1 weight percentage after rubbing back and forth 40 to 60 times with steel wool with a load greater than 200g to 400g.

[0025] The above antibacterial coating has antibacterial properties. The "antibacterial property" described herein refers to "biological inertness". In other words, after the dual-ion polymer forms an antibacterial coating on the surface of the substrate, it is difficult for pathogens and / or their vectors to be non-specifically adsorbed on the surface of the antibacterial coating. In some embodiments, pathogens may include but are not limited to fungi, bacteria and / or viruses. In some embodiments, the vectors of pathogens may include but are not limited to dust, droplets and / or aerosols carrying pathogens.

[0026] The antibacterial property can be evaluated by the relative bacterial percentage or relative antibacterial rate obtained by the antibacterial test. In some embodiments, the antibacterial test is to place the sheet (including the substrate without antibacterial coating and the substrate with antibacterial coating) in a bacterial solution, and after culturing at 35° C. to 40° C. for 20 to 30 hours, calculate the amount of bacteria on the surface of the sheet, wherein the bacteria can be, for example, Escherichia coli or Staphylococcus aureus.

[0027] The above relative bacterial percentage is the percentage of the amount of bacteria on the surface of the antimicrobial coating (i.e., N1) compared to the amount of bacteria on the surface of the substrate (without the antimicrobial coating) (i.e., N0) [i.e., (N1 / N0)×100%]. The relative antibacterial rate is the difference between 100% and the relative bacterial percentage [i.e., 100%-(N1 / N0)×100%], which is equivalent to the difference between the amount of bacteria on the surface of the substrate (i.e., N0) and the amount of bacteria on the surface of the antimicrobial coating (i.e., N1) relative to the amount of bacteria on the surface of the substrate (i.e., N0) [i.e., (N0-N1) / N0×100%]. In some embodiments, the antibacterial property is a relative bacterial percentage of less than 20%, which is equivalent to a relative antibacterial rate of greater than 80%.

[0028] The hydrophilic diionic polymer described herein includes the copolymer described in Formula 1.

[0029]

[0030] R 1 is a thioether comprising at least two acrylate groups. 1 Yes (CH2) x S(CH2) y CH(COOC2H3)2 or (CH2) x S(CH2) y CH(COOC2H3)CH2(COOC2H3), wherein x is an integer from 0 to 5, and y is an integer from 0 to 5. In some embodiments, R 1 is SCH(COOC2H3)2. In other embodiments, R 1It is (CH2)S(CH2)4CH(COOC2H3)CH2(COOC2H3). 1 With at least two acrylate groups, the diionic polymer can not only be hydrophilic, but also form an antibacterial coating with good adhesion.

[0031] R 2 and R 3 is a hydrogen atom or a methyl group. 4 are COOR' and CONR", and R' and R" are betaine, sulfobetaine, carboxybetaine or derivatives thereof, so that the formed antibacterial coating has antibacterial properties. In some specific examples, the diionic polymer includes a copolymer as shown in Formula 2, Formula 3 or Formula 4.

[0032]

[0033] In some embodiments, the average molecular weight of the diionic polymer may be, for example, 5,000 to 10,000, so that after the diionic polymer is treated with water plasma, the antibacterial coating formed is easier to graft onto the surface of the substrate to form a film, and the weight density of the diionic polymer contained in the antibacterial coating is sufficient to make the antibacterial coating biologically inert and antibacterial.

[0034] The method for preparing the diionic polymer is briefly described as follows. First, a starting material is provided, wherein the starting material comprises a first monomer and a second monomer. The first monomer comprises a thioether having at least two hydroxyl groups. In some embodiments, the first monomer is CH2CH(CH2) m S(CH2) n CH(OH)2 or CH2CH(CH2) m S(CH2) n CHOHCH2OH, m is an integer from 0 to 5, and n is an integer from 0 to 5. In some embodiments, the first monomer may be obtained by reacting alkenyl mercaptan with alkenyl epoxy compound under alkaline catalysis. In some specific examples, the first monomer is obtained by reacting allyl mercaptan with glycidol under the catalysis of triethylamine (TEA).

[0035] The second monomer includes a betaine group, an alkyl betaine group, a sulfo betaine group, or a carboxy betaine group. In some embodiments, the second monomer may be obtained by reacting an aliphatic tertiary amine with a sulfonic acid. In some specific examples, the second monomer is obtained by reacting 2-(2-dimethylamino) methacrylate with 1,3-propane sultone.

[0036] Then, the starting material is subjected to a first polymerization step. The first polymerization step may be, for example, an atom transfer radical polymerization method. In some embodiments, the first polymerization step is carried out in an anaerobic, inert gas environment (e.g., nitrogen, helium, or argon), using ethanol as a solvent, copper bromide / bipyridine (CuBr / 2,2'-bipyridine; CuBr / bpy) as a catalyst, and methyl 2-bromopropionate (MBrP) as a polymerization initiator.

[0037] Next, an olefin compound containing an acyl halide group is added, and a second polymerization step is performed. In some embodiments, the olefin compound containing an acyl halide group may include but is not limited to an acyl chloride group or an acyl bromide group. In some specific examples, the olefin compound containing an acyl halide group is propyl olefin chloride. In some embodiments, the second polymerization step may be performed under the catalysis of triethylamine.

[0038] The above-mentioned manufacturing method can produce a highly hydrophilic dual-ion polymer as shown in the above formula 1. Experiments have confirmed that the contact angle between the antibacterial coating formed by the dual-ion polymer and water is 10° to 40°.

[0039] Since the diionic polymer of the present invention has high hydrophilicity, it can be dissolved in water, and through water plasma treatment, the diionic polymer has free radicals, which helps to form an antibacterial coating with good adhesion on the substrate. The method for water plasma treatment is briefly described as follows. First, the diionic polymer is formulated into a diionic polymer aqueous solution. In some embodiments, the content of the diionic polymer in the diionic polymer aqueous solution is 30 weight percent to 50 weight percent, so that after the diionic polymer is treated with water plasma, the antibacterial coating formed is easier to graft with the surface of the substrate to form a film, and the weight density of the diionic polymer contained in this antibacterial coating is sufficient to make the antibacterial coating biologically inert and antibacterial.

[0040] The diionic polymer has high hydrophilicity. In some embodiments, the water contact angle of the substrate not treated with water plasma is 50° to 80°, but after the substrate is treated with water plasma of the diionic polymer, the water contact angle is 10° to 40°.

[0041] Next, the dual-ion polymer aqueous solution is ionized by gas plasma to obtain a plasma-activated dual-ion polymer aqueous solution. The gas plasma can be obtained by plasma treatment of air or oxygen, for example. The plasma treatment can be performed by existing methods, such as low-temperature vacuum plasma or low-temperature atmospheric pressure plasma. In some specific examples, the low-temperature atmospheric pressure plasma can include but is not limited to jet plasma, dielectric layer discharge or corona discharge.

[0042] The ionization treatment may be, for example, to pass gas plasma into a tank containing a dual-ion polymer aqueous solution, so that the dual-ion polymer in the dual-ion polymer aqueous solution has free radicals to enhance its reactivity, thereby helping to form an antibacterial coating with good adhesion on the surface of the substrate.

[0043] In some embodiments, the ionization treatment can be performed at room temperature and normal pressure, wherein the room temperature can be, for example, 5°C to 50°C, or 10°C to 45°C, or 15°C to 35°C, or 20°C to 30°C. In some embodiments, the normal pressure can be, for example, 0.5 atmospheres (atm) to 1.5 atmospheres, or 0.8 atmospheres to 1.2 atmospheres. In some embodiments, the time of the ionization treatment can be, for example, 5 minutes to 120 minutes, such as: 10 minutes to 60 minutes, or 20 minutes to 60 minutes.

[0044] Then, the substrate is immersed in the plasma activated diionic polymer aqueous solution so that the diionic polymer in the plasma activated diionic polymer aqueous solution is grafted on the surface of the substrate to form an antibacterial coating. In some embodiments, the immersion time is not particularly limited, and can be, for example, 5 minutes to 120 minutes, so that the diionic polymer can be appropriately entangled, and the formed antibacterial coating can have better antibacterial properties. In some embodiments, the thickness of the antibacterial coating can be, for example, 0.5 μm to 50 μm.

[0045] In some embodiments, before immersing the substrate in the plasma activated dual ion polymer aqueous solution, the substrate is first subjected to plasma surface treatment to enhance the reactivity of the substrate surface. The plasma surface treatment includes using conventional plasma treatment. Conventional plasma treatment has been listed above and will not be described in detail here.

[0046] The substrate may be an existing material used to make eyeglass lenses, such as glass, polycarbonate (PC), triacetate cellulose film (TCF), nylon, poly(acrylic acid) diglycol ester (CR-39), polymethylmethacrylate (PMMA), polyethylene terephthalate (PET) or polypropylene (PP).

[0047] In some embodiments, the substrate surface may further have a multi-layer anti-reflective coating (AR), wherein the material of the multi-layer anti-reflective layer may be, for example, titanium dioxide, silicon dioxide, zirconium dioxide or magnesium fluoride. In other words, the antibacterial coating formed by the dual-ion polymer may be formed on the surface of the outermost anti-reflective layer.

[0048] According to the antibacterial test, the relative antibacterial rate of the antibacterial coating formed by the dual-ion polymer is greater than or equal to 80% compared to the substrate without the antibacterial coating, which is indeed antibacterial and can be used to prepare the antibacterial coating composition. Secondly, compared with the antibacterial coating formed by the coating method of the existing polymer materials (including dual-ion fragments and long-chain non-ionic fragments) with poor hydrophilicity, the antibacterial coating formed by the dual-ion polymer of the present invention through water plasma treatment has better antibacterial adhesion to the substrate.

[0049] It should be noted that the existing plasma treatment (such as plasma-assisted chemical vapor deposition process) requires first heating the material to be deposited on the surface of the substrate to 40°C to 80°C to form a gaseous material, and then using a carrier gas to make the gaseous material flow into the cavity so that the gaseous material is deposited and grafted on the surface of the substrate. However, the diionic polymer is difficult to vaporize, so it is impossible to form an antibacterial coating using the existing plasma treatment (such as plasma-assisted chemical vapor deposition process). Because the diionic polymer of the present invention has high hydrophilicity and reactive functional groups, the diionic polymer can be grafted on the surface of the substrate through water plasma treatment, thereby improving the durability of the antibacterial and anti-fog layer obtained.

[0050] Several embodiments are used below to illustrate the application of the present invention, but they are not used to limit the present invention. Those skilled in the art of the present invention can make various changes and modifications without departing from the spirit and scope of the present invention.

[0051] Preparation Example 1

[0052] First, a monomer 1 as shown in Formula 5 is prepared, which is prepared by polymerization of allyl mercaptan and glycidol in ethyl acetate under the catalysis of triethylamine (TEA).

[0053]

[0054] Next, a monomer 2 represented by Formula 6 was prepared, which was prepared by reacting 2-(2-dimethylamino) methacrylate with 1,3-propane sultone in an acetone solvent by betaining for 24 hours.

[0055]

[0056] Then, in a nitrogen environment, using ethanol as a solvent, cuprous bromide / bipyridine (CuBr / bpy) as a catalyst, and methyl 2-bromopropionate (MBrP) as a polymerization initiator, monomer 1 and monomer 2 are subjected to atom transfer radical polymerization to form polymer 1 as shown in Formula 7.

[0057]

[0058] Next, triethylamine was used to catalyze the reaction of polymer 1 and propylvinyl chloride to obtain a diionic polymer (as shown in Formula 2). Then, the diionic polymer was prepared into a 40 weight percent diionic polymer aqueous solution. Air plasma was prepared using low-temperature atmospheric pressure plasma, and then the air plasma was passed into the diionic polymer aqueous solution at 25° C. and 1 atmosphere to perform ionization treatment for 15 minutes, thereby obtaining a plasma-activated diionic polymer aqueous solution.

[0059] The lens is subjected to plasma surface treatment for 10 to 60 minutes by low-temperature atmospheric pressure plasma. The lens is a commercially available corrective lens, comprising a substrate and an anti-reflective layer, wherein the substrate is poly(allyl diglycol carbonate) (CR-39) and the anti-reflective layer is silicon dioxide. The plasma-surface-treated lens is immersed in a plasma-activated diionic polymer aqueous solution for 20 to 60 minutes to form a coating on the surface of the lens, thereby preparing the sheet of Preparation Example 1. It is worth noting that although Preparation Example 1 only uses the diionic polymer comprising the polymer shown in Formula 2 as an example, the diionic polymer comprising the polymer shown in Formula 3 and Formula 4 or other similar polymers with similar structures are used to prepare the sheet, and the same evaluation method is used. The results obtained should be the same as those of Preparation Example 1, and will not be repeated here.

[0060] Preparation of Comparative Example 1

[0061] The sheet of Preparation Comparative Example 1 is the lens of Preparation Example 1, but is not immersed in the plasma-activated dual-ion polymer aqueous solution.

[0062] Preparation of Comparative Example 2

[0063] The sheet prepared in Comparative Example 2 is the same as that prepared in Example 1, except that the diionic polymer prepared in Comparative Example 2 comprises a polymer 2 as described in Formula 8, which is prepared using methanol allyl sulfide as a monomer 1, wherein the monomer 1 has only one acrylate group.

[0064]

[0065] Preparation of Comparative Example 3

[0066] The sheet material of Comparative Example 3 is prepared in the same manner as that of Preparation Example 1, except that the coating of Comparative Example 3 is formed by immersing the sheet material in a coating composition and drying it at 120° C. for 30 minutes. The coating composition comprises a polymer 3 represented by Formula 9 and vinyltrimethoxysilane, which are polymerized at 60° C., and p in Formula 9 is 14.

[0067]

[0068] Evaluation methods and results

[0069] Contact angle

[0070] 5 μL of water was dropped on the sheets of Preparation Example 1 and Preparation Comparative Examples 1 to Preparation Comparative Examples 3, respectively, and the contact angle was measured at 25° C. using an automatic contact angle measuring instrument.

[0071] Antibacterial test

[0072] The antibacterial property of the sheet of Preparation Example 1 was evaluated. First, the front and back sides of the sheet of Preparation Example 1 were irradiated with ultraviolet light for 5 minutes each to sterilize the sheet of Preparation Example 1, wherein the front side of the sheet of Preparation Example 1 refers to the side where the number of bacteria on the surface is sampled in subsequent experiments. Next, the sheet of Preparation Example 1 was placed face up in a culture dish containing bacterial solution, and the bacteria were cultured at 37°C for 24 hours, so that the bacterial concentration in the bacterial solution was 2.5×10 5 Colony-forming unit (CFU) / mL to 10.0×10 5 CFU / mL.

[0073] Then, the sheet of Preparation Example 1 was taken out from the culture dish, and after removing the liquid visible to the naked eye, the sheet of Preparation Example 1 was washed, and the liquid on the surface of the sheet of Preparation Example 1 was drained. The washing method was to soak the sheet in phosphate buffered saline (PBS) for 5 minutes, and then soak the sheet in fresh PBS. Next, 10 mL of lecithin and 80% soybean casein digestlecithin polysorbate 80 medium (SCDLP) was used to rinse the front of the test piece to obtain a rinse solution. 1 mL of the rinse solution was applied to the culture medium and cultured at 37°C for 24 hours, and then the number of colonies in the culture medium (i.e., N1) was calculated. The number of colonies in Preparation Comparative Example 1 (i.e., N0) was obtained by the above method.

[0074] The percentage of the number of colonies in the culture medium of Preparation Example 1 (i.e., N1) to the number of colonies in the culture medium of Preparation Comparative Example 1 (i.e., N0) was calculated [i.e., (N1 / N0)×100%] to obtain the relative bacterial percentage of Preparation Example 1. Then, the difference between 100% and the relative bacterial percentage of Preparation Example 1 was calculated [i.e., 100%-(N1 / N0)×100%] to obtain the relative antibacterial rate.

[0075] Next, the relative bacterial percentages of Preparation Comparative Example 2 and Preparation Comparative Example 3 relative to Preparation Comparative Example 1 were obtained in the same manner. It should be noted that the above-mentioned bacteria were Escherichia coli, and the culture medium was LB culture agar. The results of the antibacterial test are recorded in Table 1, where "0" indicates that the relative antibacterial rate is ≥80%, which is antibacterial, and "╳" indicates that the relative antibacterial rate is <80%, which is not antibacterial.

[0076] Hundred Grid Test

[0077] First, a scoring area was set on the surface of the sheet of Preparation Example 1, and a blade was used to score several first scoring lines with a spacing of 1 mm on the surface of the sheet of Preparation Example 1 in the scoring area with a stable pressure. Then, a blade was used to score several second scoring lines with a spacing of 1 mm on the surface of the sheet of Preparation Example 1 in the scoring area with the same pressure, wherein the first scoring lines were perpendicular to the second scoring lines, and the first scoring lines and the second scoring lines formed a plurality of squares. It should be noted that the depth of the first scoring lines and the second scoring lines is the thickness of the coating.

[0078] Next, after the tape was attached to the surface of the sheet in the engraved area for 60 seconds, the tape was torn off at nearly 180 degrees, and the surface of the sheet in the engraved area was observed with a magnifying glass. The evaluation results are recorded in Table 1, where "0" indicates that the surface of the sheet in the square formed by the first and second engraved lines is not peeled off, or the surface of the sheet is peeled off only around the first or second engraved lines or at the intersection of the first and second engraved lines, and the peeling area is less than 5%, and "╳" indicates that there is serrated peeling on both sides of the first or second engraved lines, or the surface of the sheet in the square formed by the first and second engraved lines is peeled off, or the surface of the sheet outside the engraved area is peeled off.

[0079] Steel wool test to assess adhesion

[0080] The first steel wool test is to first measure the weight of the sheet of Preparation Example 1, and then rub the surface of the sheet of Preparation Example 1 back and forth 20 times with steel wool weighing 200 g, and then measure the weight of the sheet of Preparation Example 1. The difference between the weight of the sheet of Preparation Example 1 before and after the friction treatment and the percentage of the weight before the friction treatment are calculated to obtain the weight loss rate.

[0081] The second steel wool test is to first measure the weight of the sheet of Preparation Example 1, and then rub the surface of the sheet of Preparation Example 1 back and forth 60 times with steel wool weighing 400 g, and then measure the weight of the sheet of Preparation Example 1. The difference between the weight of the sheet of Preparation Example 1 before and after the friction treatment and the percentage of the weight before the friction treatment are calculated to obtain the weight loss rate.

[0082] The weight loss rates of the sheets of Comparative Examples 1 to 3 were evaluated in the same manner. The smaller the weight loss rate, the better the durability of the coating film. The results are recorded in Table 1, where "○" indicates a weight loss rate of <1%, good durability, and "╳" indicates a weight loss rate of ≥1%, poor durability.

[0083] Table 1

[0084]

[0085] N / A means not assessed, not applicable

[0086] As shown in Table 1, the sheet of Preparation Example 1 has antibacterial properties and the coating has adhesion. The surface of the sheet of Preparation Comparative Example 1 has no coating, and the surface of the sheet is easy to fall off after being subjected to external force. The coating of the sheet of Preparation Comparative Example 2 has fewer acrylate groups in the double ion polymer, and although it has antibacterial properties, the adhesion of the coating is poor. The coating of the sheet of Preparation Comparative Example 3 is formed by coating the coating composition, and has antibacterial properties and adhesion, but its adhesion is poorer than that of the coating of Preparation Example 1.

[0087] It can be seen from the above embodiments that the dual-ion polymer of the present invention, its preparation method and the antibacterial coating composition containing the same have the advantages that the dual-ion polymer used contains an acrylate group, has high hydrophilicity, and can be dissolved in water. Therefore, it can be treated with water plasma to make the dual-ion polymer have free radicals, which helps to form an antibacterial coating with good adhesion on the surface of the substrate.

[0088] Although the present invention has been disclosed as above with several specific embodiments, various modifications, changes and substitutions may be made to the aforementioned disclosure, and it should be understood that in some cases, certain features of the embodiments of the present invention will be adopted but other features will not be used accordingly without departing from the spirit and scope of the present invention. Therefore, the spirit and scope of the claims of the present invention should not be limited to the above exemplary embodiments.

Claims

1. A diionic polymer comprising a copolymer according to formula 1, characterized in that: R 1 is a thioether containing at least two acrylate groups; R 2 and R 3 is a hydrogen atom or a methyl group; R 4 are COOR' and CONR", and R' and R" are betaine, sulfobetaine or carboxybetaine.

2. The dual ion polymer according to claim 1, characterized in that Where R 1 Yes (CH2) x S(CH2) y CH(COOC2H3)2 or (CH2) x S(CH2) y CH(COOC2H3)CH2(COOC2H3), x is an integer from 0 to 5, and y is an integer from 0 to 5.

3. The dual ion polymer according to claim 1, characterized in that The average molecular weight of the diionic polymer is 5,000 to 10,000.

4. The dual ion polymer according to claim 1, characterized in that The contact angle of the antibacterial coating formed by the double ion polymer to water is 10° to 40°.

5. A method for producing a diionic polymer, characterized in that: Include: Providing a starting material, wherein the starting material comprises: A first monomer, a thioether comprising at least two hydroxyl groups; and a second monomer comprising a betaine group, a sulfobetaine group or a carboxybetaine group; The starting material is subjected to a first polymerization step, an olefin compound containing an acyl halide group is added, and a second polymerization step is performed to obtain the dual ion polymer.

6. The method for producing a dual ionic polymer according to claim 5, characterized in that: Wherein the first monomer is CH2CH(CH2) m S(CH2) n CH(OH)2 or CH2CH(CH2) m S(CH2) n CHOHCH2OH, m is an integer from 0 to 5, and n is an integer from 0 to 5.

7. The method for producing a dual ionic polymer according to claim 5, characterized in that: The acyl halide group comprises an acyl chloride group or an acyl bromide group.

8. The method for producing a dual ionic polymer according to claim 5, characterized in that: The molar ratio of the first monomer to the second monomer is 2:3 to 3:

2.

9. An antibacterial coating composition, characterized in that: The invention comprises the dual ionic polymer according to any one of claims 1 to 4.

10. The antibacterial coating composition according to claim 9, characterized in that: Wherein, based on the usage of the antibacterial coating composition being 100 weight percent (wt%), the usage of the dual ion polymer is 30 weight percent to 50 weight percent.